Bond-bending isomerism of Au2I3−: competition between covalent bonding and aurophilicity. Issue 1 (22nd October 2015) - Li, Wan-Lu; Liu, Hong-Tao; Jian, Tian; Lopez, Gary V.; Piazza, Zachary A.; Huang, Dao-Ling; Chen, Teng-Teng; Su, Jing; Yang, Ping; Chen, Xin; Wang, Lai-Sheng; Li, Jun
Abstract : Two isomers, different only by bond angles, are discovered for Au2 I3 −, due to competition between aurophilic interactions and covalent bonding. Abstract : We report a joint photoelectron spectroscopy and theoretical investigation of the gaseous Au2 I3 − cluster, which is found to exhibit two types of isomers due to competition between Au–I covalent bonding and Au–Au aurophilic interactions. The covalent bonding favors a bent IAuIAuI − structure with an obtuse Au–I–Au angle (100.7°), while aurophilic interactions pull the two Au atoms much closer, leading to an acutely bent structure (72.0°) with an Au–Au distance of 3.08 Å. The two isomers are separated by a small barrier and are nearly degenerate with the obtuse isomer being slightly more stable. At low temperature, only the obtuse isomer is observed; distinct experimental evidence is observed for the co-existence of a combination of isomers with both acute and obtuse bending angles at room temperature. The two bond-bending isomers of Au2 I3 − reveal a unique example of one molecule being able to oscillate between different structures as a result of two competing chemical forces.